Odpowiedzi

  • Użytkownik Zadane
2009-11-10T21:13:19+01:00
Ω = { (1,1) ; (1, 2) ; (1, 3) ; (1, 4) ; (1, 5) ; (1,6) ; (2, 1) ; (2,2) ; ... ; (6; 5) ; (6, 6) }
A = { (1, 5) ; (2, 4) ; (3, 3) ; (4, 2) ; (5, 1)}
B = { (1, 1) }
Zbiory A i B są rozłączne tzn że A (iloczyn) B = zbiór pusty
A (suma) B = {(1, 1) ; (1, 5) ; (2, 4) ; (3, 3) ; (4, 2) ; (5, 1)}
A\B = A = { (1, 5) ; (2, 4) ; (3, 3) ; (4, 2) ; (5, 1)} bo są zbiorami rozłącznymi

P(A suma B) = P(A) + P(B) - P(A iloczyn B)
P(A suma B) = P(A) + P(B) - P(zbiór pusty) = P(A) + P(B) + 0 = (5/36) + (1/36) = (6/36) = (1/6)
P(A iloczyn B) = P (zbiór pusty) = 0
P(A/B) = P(A) = 5/36
Chyba jakoś tak :)
1 5 1